2019
DOI: 10.3390/coatings9040230
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Properties of Protective Coatings Deposited by Pulsed Cathodic Arc Evaporation in Ar, N2, and C2H4 Environments using the TiC–NiCr–Eu2O3 Cathode

Abstract: Coatings were deposited by pulsed cathodic arc evaporation (PCAE) of a TiC–NiCr–Eu2O3 cathode fabricated by the powder metallurgy method. The deposition was carried out in different gas media, including Ar, N2, and C2H4. The structure, elemental, and phase compositions of coatings were studied by scanning electron microscopy (SEM), X-ray diffraction (XRD), energy-dispersive spectroscopy (EDS), Raman spectroscopy, and glow discharge optical emission spectroscopy (GDOES). Coatings were tested in terms of their h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 60 publications
0
3
0
2
Order By: Relevance
“…Earlier, we demonstrated that the introduction of Eu 2 O 3 into the electrode composition leads to the increase in their strength [32], coating growth rate [33], mechanical/tribological properties, and corrosion resistance of the coatings [34,35]. The introduction of additional carbon, for example, from a reactive atmosphere, and the formation of diamond-like carbon allow one to reduce the friction coefficient and enhance the corrosion resistance of coatings [32]. Sputtering of the upper diamond-like carbon (DLC) layer on the arc-deposited base TiC coatings increased the hardness and elastic modulus by 60% and 20%, respectively [36].…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Earlier, we demonstrated that the introduction of Eu 2 O 3 into the electrode composition leads to the increase in their strength [32], coating growth rate [33], mechanical/tribological properties, and corrosion resistance of the coatings [34,35]. The introduction of additional carbon, for example, from a reactive atmosphere, and the formation of diamond-like carbon allow one to reduce the friction coefficient and enhance the corrosion resistance of coatings [32]. Sputtering of the upper diamond-like carbon (DLC) layer on the arc-deposited base TiC coatings increased the hardness and elastic modulus by 60% and 20%, respectively [36].…”
Section: Introductionmentioning
confidence: 90%
“…The introduction of ZrO 2 , Al 2 O 3 , NbC, WC, and other additives into TiC-Ni and TiC-NiCr electrodes allows one to increase the coating growth rate, hardness, and heat resistance as well as to decrease the coefficient of friction [2]. Earlier, we demonstrated that the introduction of Eu 2 O 3 into the electrode composition leads to the increase in their strength [32], coating growth rate [33], mechanical/tribological properties, and corrosion resistance of the coatings [34,35]. The introduction of additional carbon, for example, from a reactive atmosphere, and the formation of diamond-like carbon allow one to reduce the friction coefficient and enhance the corrosion resistance of coatings [32].…”
Section: Introductionmentioning
confidence: 92%
“…In this research work, the corrosion protection large surfaces in a marine environment. Moreover, the work in [21] discussed the coatings deposited via pulsed cathodic arc evaporation (PCAE) of a TiC-NiCr-Eu 2 O 3 cathode fabricated by the powder metallurgy method. The deposition was carried out in different gas media, including Ar, N 2 , and C 2 H 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Ранее нами было показано, что введение Eu 2 O 3 в состав электродов TiCNiCr позволяет повысить их прочностные характеристики [11], скорость роста покрытий [12], а также механические и трибологические свойства покрытий [13]. В настоящей работе были увеличены (в 4 раза) концентрации хрома и никеля по сравнению с предыдущими исследованиями.…”
Section: Introductionunclassified
“…В настоящей работе были увеличены (в 4 раза) концентрации хрома и никеля по сравнению с предыдущими исследованиями. Перспективным для нанесения покрытий является метод импульсного катодно-дугового испарения [12] с использованием данных электродов, впервые предложенный в работе [14].…”
Section: Introductionunclassified